Load Flow Analysis at Babakan Substations for Industry Growth Devolopment Using ETAP Power Station 12.6 Softwere - Erfan Subiyanta; Muhammad Fadhil Aldan; Muhamad Soleh (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2022)
Based on transformer loading at GI 70kV Babakan which is already 80% high bigger than capacity 30 MVA by reason there is a need for additional power supply for industrial development, one of which is the addition of PT. Longrich Indonesia for 25 MVA. With the existing condition of transformer loading at GI 70kV Babakan is currently unable to meet the power supply needs and the construction of GI 150kV Kanci is still in progress, therefore the installation of a mobile transformer at GI 70kV Babakan is intended to meet the need for additional power supply. In this study, simulating Electrical power in GI 70kV Babakan uses the ETAP Power Station 12.6 software and compares it with the results of manual calculations. Installing a Mobile Transformer with a capacity of 30 MVA at GI 70kV Babakan can increase the MVA capacity at GI 70kV Babakan so that it can meet the need for additional power supply, With the load on the mobile transformer and the daytime loading history of 48 MW and the highest load reached at 61 MW, the Mobile Transformer can be loaded with a maximum of 25 MVA. And transformers are still able to supply the area properly so there is no overload. and increase revenue through the sale of electricity.